Tanggap Pertumbuhan dan Hasil Dua Genotipe Bengkuang (Pachyrhizus erosus (L.) Urban.) terhadap Pemberian Pupuk SP-36 - Septiani, Riri; Syarif, Auzar (JURNAL AGROTEKNOLOGI UNIVERSITAS ANDALAS, 2022)
Research was conducted in experimental field with the objectives were to understand the interaction of two genotypes of yam bean with SP-36 fertilizer, to determine the best dose of SP-36 fertilizer for growth and yield of yam, and to find out better genotype of yam bean on growth and yield of yam bean. The experiment was conducted in the factorial with two factors arranged in Complete Randomized Design and repeated 3 times. The first factor was 4 levels dose of fertilizer SP-36 (30, 60, 90, and 120 kg/ha). The second factor was 2 genotypes of yam bean (Batang Anai and Jember). Data were analyzed with F test and Duncan’s New Multiple Range Test (DNMRT) at 5% level of confidence. The results concluded that there was no interaction between two genotype of yam bean with application of SP-36 fertilizer on growth and yield of yam bean. Provision of several doses of SP-36 fertilizer did not affect the growth and yield of two genotypes of yam bean. The genotype of yam that showed better growth and yield was Jember.